Reconnection patterns after CLOSE‐guided 50 W high‐power‐short‐duration circumferential pulmonary vein isolation and substrate modification—PV reconnection might no longer be an issue. (15th February 2022) - Francke, Alexander; Scharfe, Frank; Schoen, Steffen; Wunderlich, Carsten; Christoph, Marian
Abstract: Introduction: Ablation of atrial fibrillation (AF) with high‐power‐short‐duration (HPSD) radiofrequency (RF) technology is emerging as a new standard of care in many electrophysiology laboratories. While procedural short‐term efficacy and efficiency is very promising, little is known about mid‐ to long‐term effects of HPSD ablation for pulmonary vein isolation (PVI) and left atrial substrate modification. Methods: In a single‐center registry, 412 AF procedures were performed in 400 individual patients using a standardized CLOSE protocol‐guided fixed 50 W HPSD ablation, aiming for an ablation index (AI) of 400 on the posterior and 550 on the anterior wall. Additional substrate‐tailored lines were performed when required. Results: After a mean clinical follow‐up of 337 ± 134 days, 15 patients suffered from AF recurrence beyond the blinding period. Twelve gave consent to the indicated reablation. Here, 11 of 12 patients had chronic isolation of all four pulmonary veins (PV). In three of six patients, a reconnection of additional left atrial ablation lines was revealed. Ten out of 12 patients showed progressive fibrous atrial cardiomyopathy and required additional left atrial substrate modification or reisolation of left‐atrial lines. During the follow‐up no clinical case of atrioesophageal fistula was registered. No PV stenosis after initial HPSD PVI was documented. Conclusions: Patients requiring reablation of AF or other atrial tachycardia after a fixed 50 W HPSD circumferential PVI and substrate modification predominantly suffer from progressive fibrous atrial cardiomyopathy, while PV reconnection appears to be a rare cause of AF recurrence.